Deficiency of the sixth component of complement and susceptibility to Neisseria meningitidis infections: studies in 10 families and five isolated cases. - Orren, A (1987)
Complement component C6 deficiency (C6D) was diagnosed in 15 patients who presented, independently, with recurrent meningococcal infection. This condition is thus not particularly rare in the Cape. Ten of the patients belonged to multiplex families, and family studies led to the diagnosis of another 12 C6D cases among the siblings. Segregation analysis showed that C6D occurred more frequently among the siblings of affected individuals than would be expected for co-dominant inheritance. The possible reasons for this are discussed. We also observed that the 12 non-proband C6D siblings included only four with a history suggestive of meningococcal infection, and thus C6D individuals apparently differ in susceptibility to Neisseria meningitidis infection. We confirmed previous observations that primary infection occurs later in C6D individuals than amongst susceptible complement-sufficient individuals. Among 123 patients presenting with primary meningitis, one case of C6D was diagnosed. The data show that C6D is an important factor associated with susceptibility to meningococcal infection in the Cape.